Peran Guru dalam Mengembangkan Literasi pada Anak Usia Dini Kelompok B TK Irama Jaya Ulapato A Kecamatan Telaga Biru Kabupaten Gorontalo - Nurhasana Nurhasana; Irvin Novita Arifin; Rapi Us Djuko (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
This study aims to investigate the role of teachers in developing literacy among early childhood learners at TK Irama Jaya Ulapato A, located in Telaga Biru District, Gorontalo Regency. The research employs a qualitative approach with a descriptive method. The subjects of the study are the teachers at TK Irama Jaya Ulapato A. Data collection techniques include observation, interviews, and documentation. The findings indicate that teachers play a significant role in fostering literacy in early childhood, particularly through storytelling activities. In its implementation, teachers act as motivators by giving praise to children who are able to answer questions as a form of positive reinforcement. As facilitators, teachers provide learning materials such as storybooks used during the learning process. Furthermore, teachers also serve as evaluators, conducting direct assessments of the children’s understanding related to literacy activities. Lastly, teachers function as class managers, creating an enjoyable learning environment and engaging activities that help increase children's interest in learning and improve their literacy skills.